Simultaneous Determination of Three Major Active Components in Salvia miltiorrhiza and its Relative Species by HPLC - Wang, Tao; Zhang, Hui; Liu, Qi; Zhang, Li; Jiang, Yuanyuan; Wang, Meng; Zhou, Yonghong; Yang, Ruiwu; Ding, Chunbang; Wang, Xiaoli (Asian Journal of Chemistry, 2013)
A high performance liquid chromatographic method was established for determination of three phenolic acids constituents (protocatechuic aldehyde, salvianolic acid B and salvianolic acid A) in 25 samples, including Salvia miltiorrhiza of different strains and its related species (S. brevilabra, S. castana, S. cavaleriei, S. cavaleriei var. simpliciflia, S. digitaloides, S. paohsingensis, S. plebeia, S. prezwalskii, S. trijuga and S. yunnanensis). The three components were successfully separated on a Shimadzu Shim-pack VP-ODS C18 reserved phase column (5 μm, 250 mm × 4.6 mm i.d.) by gradient elution using acetonitrile and 0.03 % (v/v) phosphoric acid as the mobile phase, the flow rate was 1 mL min-1 and the detection was set at 288 nm. The linearity was obtained over 0.648-99.06 μg mL-1 for protoctechuic aldehyde, 14.63-1786 μg mL-1 for salvianolic acid B and 2.561-334.14 μg mL-1 for salvianolic acid A. The average recovery rates of protoctechuic aldehyde, salvianolic acid B and salvianolic A were 95.17, 94.06 and 91.43 %, respectively. This method was successfully applied to the determination of three important phenolic acids constituents in 25 samples. The proposed method is simple, effective and suitable for quality control of S. miltiorrhiza and its relative species.